shRNA targeting long non-coding RNA CCAT2 controlled by tetracycline-inducible system inhibits progression of bladder cancer cells - Li, Jianfa (Oncotarget, 2016)
Recent reports show that long non-coding RNAs (lncRNAs) are emerging as significant functional regulators in the development of tumors, including bladder cancer. Here, we found that CCAT2 was upregulated in bladder cancer tissues and cell lines. Through the statistical analyses, we also found that the high expression level of CCAT2 was positively correlated with histological grade and TNM stage of bladder cancer. Further experimental results revealed that knockdown of CCAT2 could decrease cell proliferation and migration as well as induce apoptosis in bladder cancer cells. Besides, using the post-transcriptional device of synthetic biology, we create the tetracycline-inducible double small hairpin RNAs (shRNAs) vector to control the expression level of CCAT2 which was induced by doxycycline in a dosage-dependent manner. In summary, our data indicated that CCAT2 may be an oncogene and a therapeutic target in bladder cancer. The expression of CCAT2 can be quantitatively controlled by the synthetic “tetracycline-on” switch system in bladder cancer in response to different concentrations of doxycycline to inhibit the development of bladder cancer cells.